148k views
4 votes
Which of the following equations have no solution? Check all that apply.

6x + 1 = 3(2x – 4)
2 – 5x = 7x – 12
4(3 – x) = 2(6 – 2x)
5(x + 2) = 2(x – 4)
–4(x + 3) = 4(–x – 1)

2 Answers

1 vote

Answer:

1 and 5

Explanation:

1. 6x + 1 = 3(2x - 4)

6x + 1 = 6x - 12

6x + 13 = 6x

-6x -6x

13 = 0x

no solution

2. 2-5x = 7x - 12

2 = 12x - 12

14 = 12x

1 1/6 = x

3. 4(3 - x) = 2(6 - 2x)

12 - 4x = 12 -4x

-4x = -4x

x = ∞

4. 5(x + 2) = 2(x - 4)

5x + 10 = 2x - 8

3x + 10 = -8

3x= -18

x = -6

5. -4(x + 3) = 4( -x - 1)

-4x -12 = -4x -4

-4x - 8 = -4x

-8 = 0x

no solution

User Jainish Shah
by
4.8k points
4 votes

Answer:

–4(x + 3) = 4(–x – 1) and 6x + 1 = 3(2x – 4)

Explanation:

I copied the other dude

User Pveentjer
by
4.2k points